Integrated Nutrient Management for Potato-Maize-T. Aman Rice Cropping Pattern (Bangladesh Rice Journal, 2016)
A field experiment on integrated nutrient management (INM) for Potato-Maize-T. Aman cropping pattern was conducted at BRRI RS farm, Rangpur (AEZ-3) during 2007-2010. The objectives were to examine the effect of Potato-Maize-T. Aman cropping on soil fertility and to develop appropriate fertilizer management practices for the above mentioned pattern. Inorganic and organic nutrient sources were tested in six different combinations in Rangpur region. Poultry manure (PM) @ 3.0 t ha-1 + IPNS based inorganic fertilizers for potato (N80, P0, K30, S0, Zn0, Mg4, B1) and maize (N136, P0, K40, S2, Zn1.8, Mg2, B1) crops, and STB dose for T. Aman crop (N65, P3, K27, S8) has been recommended for Potato-Maize-T. Aman cropping pattern in Rangpur region. In fertilized plots, there was an apparent negative balance for N and K. The balances for P and S were positive. Organic C, total N and available P in soil increased due to integration of chemical fertilizer with PM. Results indicate that it is necessary to apply organic manure in combination with chemical fertilizer for sustaining soil fertility. For maize and potato crops, fertilizer dose needs to be updated after every three years of successive crop cultivation under Potato-Maize-T. Aman cropping pattern. Net additional income was the highest in T5 where PM and IPNS based fertilizer applied.Bangladesh Rice j. 2016, 20(1): 51-58